Perception of Micro Small and Medium Enterprises Performers, Accounting Understanding and Socialization on The Inplementation of Accounting Standard for Micro Small and Medium Entity - Hamdani, Deni; Kosadi, Ferry; Febriyanti, Diah (Institute Of Advanced Knowledge and Science, 2025)
The research objective is to determine the extent of the implementation Accounting Standard for MSME’s Entity to the variables that influence it by covering: perception, understanding of accounting, and socialization. Descriptive and verificative methods were used in this study with double multiple regression analysis. The research population is Handicraft MSME’s registered at the Office of Cooperatives for Micro, Small and Medium Enterprises in Bandung. Sampling using Proportional with the Slovin Formula. For Parsial results showed Perceptions of MSME actors had no effect on the application of Accounting Standard for MSME’s Entity, Accounting understanding and Socialization of Accounting Standard for MSME’s Entity had a significant influence on the application of Accounting Standard for MSME’s Entity. For Simultaneous result showed perceptions of MSME’s actors, Accounting Understanding, and Socialization of Accounting Standard for MSME’s Entity affect the Implementation of Accounting Standard for MSME’s Entity. These result hoped had implication that Accounting Standard for MSME’s Entity can be one of the drivers of financial literacy for MSME’s so that they gain wider access to financing from the banking industry.